Polymerizable liquid crystal composition and polarized film

KR1020260139007APending Publication Date: 2026-09-21SUMITOMO CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020260040563
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-12
Filing Date
2026-03-06
Publication Date
2026-09-21

Smart Images

  • Figure PAT00001
    Figure PAT00001
  • Figure PAT00002
    Figure PAT00002
  • Figure PAT00003
    Figure PAT00003
Patent Text Reader

Abstract

(Problem) To provide a polymerizable liquid crystal composition suitable for forming a polarizing film that has excellent absorbance stability when exposed to sunlight and can suppress the degradation of polarization performance over time. (Solution) Polymerizable liquid crystal compound, dichroic pigment, and formula (1): HO-A-(DB)nE (1) [Essence (1), A and B are, independently of each other, a 1,4-phenylene group that may have a substituent or a cyclohexane-1,4-diyl group that may have a substituent, and D are independently single bonds, -COO-, -OCO-, -S-, -O-, -CR=CR-, and E is a straight-chain or branched alkyl group or alkoxy group, and n is 1 or 2, and when n=1, B is a cyclohexane-1,4-diyl group that may have substituents, and when n=2, among the multiple B, at least one is a cyclohexane-1,4-diyl group that may have substituents. A polymerizable liquid crystal composition comprising an antioxidant represented by
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a polymerizable liquid crystal composition and a polarizing film formed from the polymerizable liquid crystal composition. Background Technology

[0002] Conventionally, polarizers are used in various image display panels, such as liquid crystal display panels or organic electroluminescence (organic EL) display panels, by being laminated to image display elements such as liquid crystal cells or organic EL display elements. There is a continuous demand for thinning of displays such as image display panels, and further thinning is required for polarizers and polarizers, which are one of their components. In response to this demand, for example, a thin host-guest type polarizer composed of a polymerizable liquid crystal compound and a dichroic compound has been proposed (Patent Document 1). Prior art literature

[0003] Japanese Patent Publication No. 2019-133148 The problem to be solved

[0004] In addition, as displays are recently being used in various locations, including outdoors, there is a demand for the development of polarizers with excellent light resistance.

[0005] The present invention aims to provide a polymerizable liquid crystal composition suitable for forming a polarizing film that has excellent absorbance stability when exposed to sunlight and can suppress the degradation of polarization performance over time. means of solving the problem

[0006] The inventors have completed the present invention as a result of careful consideration to solve the above problem. That is, the present invention provides the following preferred embodiments.

[0007] [1] Polymerizable liquid crystal compound, dichroic pigment, and formula (1):

[0008] HO-A-(DB) n -E (1)

[0009] [Essence (1),

[0010] A and B are, independently of each other, a 1,4-phenylene group that may have a substituent or a cyclohexane-1,4-diyl group that may have a substituent, and

[0011] D are independently single bonds, -COO-, -OCO-, -S-, -O-, -CR=CR-, and

[0012] E is a straight-chain or branched alkyl group or alkoxy group, and

[0013] n is 1 or 2, and when n=1, B is a cyclohexane-1,4-diyl group that may have substituents, and when n=2, among the multiple B, at least one is a cyclohexane-1,4-diyl group that may have substituents.

[0014] A polymerizable liquid crystal composition comprising an antioxidant represented by

[0015] [2] The polymerizable liquid crystal compound described above is a polymerizable liquid crystal composition described in [1], having a cyclohexane backbone.

[0016] [3] The above antioxidant is, formula (2):

[0017] SP3 a / ( SP2 a +SP3 a ) ≥ 0.25 (2)

[0018] [Essence (2), SP3 a is the number of SP3 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP2 ais the number of SP2 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant.

[0019] A polymerizable liquid crystal composition described in [1] above that satisfies [1].

[0020] [4] The above polymerizable liquid crystal compound is, Formula (3):

[0021] U 1 -V 1 -W 1 -X 1 -Y 1 -X 2 -Y 2 -X 3 -W 2 -V 2 -U 2 (3)

[0022] [Essence (3),

[0023] X 1 , X 2 and X 3 ...independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein the hydrogen atom included in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, a C1-4 alkyl group, a C1-4 fluoroalkyl group, a C1-4 alkoxy group, a cyano group, or a nitro group, and the carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom (provided that X 1 , X 2 and X 3 At least one of them is a cyclohexane-1,4-diyl group that may have a substituent),

[0024] Y 1 and Y 2 is, independently of each other, a single coupling or a 2-valent connector, and

[0025] U 1Representing silver, hydrogen atoms, or polymerizable groups,

[0026] U 2 is a polymerizable group,

[0027] W 1 and W 2 is, independently of each other, a single coupling or a 2-valent connector, and

[0028] V 1 and V 2 [It represents an alkanedyl group having 1 to 20 carbon atoms that may have substituents independently thereof, and the -CH2- constituting the alkanedyl group may be substituted with -O-, -CO-, -S-, or NH-]

[0029] A polymerizable liquid crystal composition described in any one of [1] to [3], comprising a compound represented by [1].

[0030] [5] The above polymerizable liquid crystal compound is, formula (4):

[0031] SP3 b / ( SP2 b +SP3 b ) ≥ 0.25 (4)

[0032] [Equation (4), SP3 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 It is the number of SP3 carbons among all carbons forming the ring represented by, and SP2 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 [It is the number of SP2 carbons among all carbons forming the ring represented by]

[0033] A polymerizable liquid crystal composition satisfying [1] to [4] as described above.

[0034] [6] Formula (5) :

[0035] |(SP3 a / ( SP2 a +SP3 a ))―(SP3 b / ( SP2 b +SP3 b )| ≤ 0.30 (5)

[0036] [Essence (5), SP3 a is the number of SP3 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP2 a is the number of SP2 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP3 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 It is the number of SP3 carbons among all carbons forming the ring represented by, and SP2 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 [It is the number of SP2 carbons among all carbons forming the ring represented by]

[0037] A polymerizable liquid crystal composition satisfying [1] to [5] as described above.

[0038] [7] A polarizing film, which is a cured film of a polymerizable liquid crystal composition described in any one of [1] to [6] above.

[0039] [8] A polarizing film described in [7] above that exhibits a Bragg peak in X-ray diffraction measurements. Effects of the invention

[0040] According to the present invention, a polymerizable liquid crystal composition suitable for forming a polarizing film that has excellent absorbance stability when exposed to sunlight and can suppress the deterioration of polarization performance over time can be provided. Specific details for implementing the invention

[0041] Embodiments of the present invention will be described in detail below. Furthermore, the scope of the present invention is not limited to the embodiments described herein, and various modifications may be made within a scope that does not impede the spirit of the invention.

[0042] Polymerizable liquid crystal composition

[0043] The polymerizable liquid crystal composition of the present invention comprises a polymerizable liquid crystal compound. The polymerizable liquid crystal compound is a liquid crystal compound having at least one polymerizable group. Here, a polymerizable group refers to a group that can participate in a polymerization reaction by means of an active radical or acid generated from a polymerization initiator.

[0044] Examples of polymerizable groups in polymerizable liquid crystal compounds include vinyl groups, vinyloxy groups, 1-chlorovinyl groups, isopropenyl groups, 4-vinylphenyl groups, acryloyloxy groups, methacryloyloxy groups, oxiranyl groups, oxetanyl groups, etc. Among these, radical polymerizable groups are preferred, acryloyloxy groups, methacryloyloxy groups, vinyl groups, vinyloxy groups are more preferred, acryloyloxy groups and methacryloyloxy groups are even more preferred, and acryloyloxy groups are particularly preferred.

[0045] The liquid crystallization of the polymerizable liquid crystal compound may be either thermotropic or lyotropic; however, thermotropic liquid crystals are preferred from the perspective of mixing with the dichroic pigments described later and the ability to control the dense film thickness. When the polymerizable liquid crystal compound is a thermotropic liquid crystal, it may be a thermotropic liquid crystal compound exhibiting a nematic liquid crystal phase or a thermotropic liquid crystal compound exhibiting a smectic liquid crystal phase. When a polarizing function is exhibited as a cured film through a polymerization reaction, it is preferable that the polymerizable liquid crystal compound be a compound exhibiting smectic liquid crystallization. By using a polymerizable liquid crystal compound exhibiting smectic liquid crystallization, a polarizing film with a high degree of orientation order can be formed. From the perspective of realizing a higher degree of orientation order, it is more preferable that the liquid crystal state exhibited by the polymerizable liquid crystal compound be a higher-order smectic phase (higher-order smectic liquid crystal state). Here, higher-order smectic phases refer to smectic B phase, smectic D phase, smectic E phase, smectic F phase, smectic G phase, smectic H phase, smectic I phase, smectic J phase, smectic K phase, and smectic L phase, among which smectic B phase, smectic F phase, and smectic I phase are more preferred. Additionally, the polymerizable liquid crystal compound may be a monomer, or an oligomer and / or polymer in which the polymerizable group is polymerized.

[0046] As for the polymerizable liquid crystal compound, any known polymerizable liquid crystal compound having at least one polymerizable group is not particularly limited.

[0047] Examples of polymerizable liquid crystal compounds include, for instance, the compound represented by formula (3) and the polymer of the compound (hereinafter, the compound and the polymer are collectively referred to as “polymerizable liquid crystal compound (3)”).

[0048] U 1 -V 1 -W 1 -X 1 -Y 1-X 2 -Y 2 -X 3 -W 2 -V 2 -U 2 (3)

[0049] [Essence (3),

[0050] X 1 , X 2 and X 3 ...independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein the hydrogen atom included in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, a C1-4 alkyl group, a C1-4 fluoroalkyl group, a C1-4 alkoxy group, a cyano group, or a nitro group, and the carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. provided that X 1 , X 2 and X 3 At least one of them is a 1,4-phenylene group that may have a substituent or a cyclohexane-1,4-diyl group that may have a substituent.

[0051] Y 1 and Y 2 It is a single coupling or a two-linker, independently of each other.

[0052] U 1 It represents a hydrogen atom or a polymerizable group.

[0053] U 2 represents a polymerizable group.

[0054] W 1 and W 2 It is a single coupling or a two-linker, independently of each other.

[0055] V 1 and V 2[It represents an alkanedyl group having 1 to 20 carbon atoms that may have substituents independently thereof, and the -CH2- constituting the alkanedyl group may be substituted with -O-, -CO-, -S-, or NH-.]

[0056] In the polymerizable liquid crystal compound (3), X 1 , X 2 and X 3 is independently, preferably a 1,4-phenylene group that may have a substituent, or a cyclohexane-1,4-diyl group that may have a substituent, and X 1 , X 2 and X 3 At least one of them is a 1,4-phenylene group that may have a substituent, or a cyclohexane-1,4-diyl group that may have a substituent. In one embodiment of the present invention, for the sake of compatibility with antioxidants and / or dichroic pigments, it is preferable that the polymerizable liquid crystal compound has a cyclohexane backbone, and X in formula (3). 1 , X 2 and X 3 It is preferable that at least one of them is a cyclohexane-1,4-diyl group having a substituent. In particular, X 1 or X 3 It is preferable that the cyclohexane-1,4-diyl group may have a substituent, and it is even more preferable that the cyclohexane-1,4-diyl group be a trans-cyclohexane-1,4-diyl group. Examples of optional substituents for the 1,4-phenylene group which may have a substituent, or for the cyclohexane-1,4-diyl group which may have a substituent, include C1 to C4 alkyl groups such as methyl, ethyl, and butyl groups, cyano groups, and halogen atoms such as chlorine and fluorine atoms. Preferably, it is unsubstituted. Also, Y 1 and Y 2 If it has the same structure, X 1 , X 2 and X 3It is desirable that at least one of them has a different structure. X 1 , X 2 and X 3 If at least one of them has a different structure, smectic liquid crystallization tends to be easily expressed.

[0057] Y 1 and Y 2 is, independently of each other, -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, single bond, -N=N-, -CR a =CR b -, -C≡C-, -CR a =N- or -CO-NR a - is desirable. R a and R b represents, independently of each other, a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. Y 1 It is more preferable that it be -CH2CH2-, -COO-, or a single bond, and Y 2 It is more preferable that it be -CH2CH2- or CH2O-. Also, X 1 , X 2 and X 3 If all of these have the same structure, Y 1 and Y 2 It is desirable that they have different structures. Y 1 and Y 2 When the structures are different from each other, smectic liquid crystallization tends to be easily expressed.

[0058] U 2 is a polymerizable group. U 1 It is silver, a hydrogen atom, or a polymerizable group, preferably a polymerizable group. U 1 and U 2 It is desirable that it is a polymerizable group, and it is desirable that it is a radical polymerizable group. As polymerizable groups, the same as the groups previously exemplified as polymerizable groups possessed by polymerizable liquid crystal compounds can be cited. U 1 The polymerizable group represented by and U 2The polymerizable groups represented by [the symbol] may be different from each other, but it is preferable that they be of the same type.

[0059] W 1 and W 2 In addition, independently, a single bond, -O-, -S-, -COO-, or -OCOO- is preferred, and a single bond or -O- is more preferred.

[0060] V 1 and V 2 Examples of alkanedyl groups represented by V include methylene groups, ethylene groups, propane-1,3-diyl groups, butane-1,3-diyl groups, butane-1,4-diyl groups, pentane-1,5-diyl groups, hexane-1,6-diyl groups, heptane-1,7-diyl groups, octane-1,8-diyl groups, decane-1,10-diyl groups, tetradecane-1,14-diyl groups, and icosan-1,20-diyl groups. 1 and V 2 The is preferably an alkanedyl group having 2 to 12 carbon atoms, and more preferably an alkanedyl group having 6 to 12 carbon atoms.

[0061] The alkandyl group may optionally have substituents such as cyano groups and halogen atoms, but it is preferable that the alkandyl group be unsubstituted, and it is more preferable that it be an unsubstituted straight-chain alkandyl group.

[0062] The polymerizable liquid crystal compound (3) preferably has a cyclohexane backbone, and more preferably has a trans-cyclohexane-1,4-diyl group. As for the polymerizable liquid crystal compound (3), one type may be used alone, or two or more types may be used in combination.

[0063] Polymerizable liquid crystal compound (3) can be manufactured by a known method described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996), or Japanese Patent No. 4719156, etc.

[0064] In one embodiment of the present invention, the polymerizable liquid crystal compound (3) is, formula (4):

[0065] SP3 b / ( SP2 b +SP3 b ) ≥ 0.25 (4)

[0066] [Equation (4), SP3 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 It is the number of SP3 carbons among all carbons forming the ring represented by, and SP2 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 [It is the number of SP2 carbons among all carbons forming the ring represented by]

[0067] It is preferable that the polymerizable liquid crystal compound satisfies the following. Here, SP3 carbon refers to a carbon atom bonded to four atoms in an SP3 hybrid orbital, for example, 6 atoms if it is a cyclohexane-1,4-diyl group, and 0 atoms if it is a 1,4-phenylene group. Also, SP2 carbon refers to a carbon atom bonded to three atoms in an SP2 hybrid orbital, for example, 0 atoms if it is a cyclohexane-1,4-diyl group, and 6 atoms if it is a 1,4-phenylene group. Hereinafter, the SP3 carbon and SP2 carbon in the antioxidant are also the same. If a polymerizable liquid crystal compound (3) satisfying formula (4) is included as a polymerizable liquid crystal compound, the polymerizable liquid crystal compound is easily oriented in an orderly manner together with the antioxidant represented by formula (1) (hereinafter also referred to as "antioxidant (1)"), and the intermolecular distance between the dichroic pigment and the antioxidant (1) can be reduced. Thus, the antioxidant (1) acts sufficiently, leading to an improvement in the photodegradation suppression effect of the dichroic pigment. SP3 in Equation (4) b / ( SP2 b+SP3 b The value of ) is more preferably 0.30 or higher, and typically 1.00 or lower.

[0068] When a polymerizable liquid crystal composition comprises two or more polymerizable liquid crystal compounds (3), it is preferable that at least one of them is a polymerizable liquid crystal compound satisfying the formula (4), and in one embodiment of the present invention, it is more preferable that all of them are polymerizable liquid crystal compounds satisfying the formula (4). In one embodiment of the present invention, the content of the polymerizable liquid crystal compound satisfying the formula (4) is preferably 51 mass% or more, more preferably 70 mass% or more, and even more preferably 90 mass% or more, based on the total mass of the polymerizable liquid crystal compounds, and the total polymerizable liquid crystal compound in the polymerizable liquid crystal composition may be a polymerizable liquid crystal compound satisfying the formula (4).

[0069] The polymerizable liquid crystal composition of the present invention may include other polymerizable liquid crystal compounds other than the polymerizable liquid crystal compound (3) as long as they do not impede the effects of the present invention. From the perspective of obtaining a polarizing film with a high degree of orientation order, the ratio of the polymerizable liquid crystal compound (3) to the total mass of all polymerizable liquid crystal compounds in the polymerizable liquid crystal composition is preferably 51 mass% or more, more preferably 70 mass% or more, and even more preferably 90 mass% or more, and the total polymerizable liquid crystal compound in the polymerizable liquid crystal composition may be the polymerizable liquid crystal compound (3).

[0070] When the polymerizable liquid crystal composition of the present invention comprises two or more polymerizable liquid crystal compounds, at least one of them may be a polymerizable liquid crystal compound (3), and all of them may be polymerizable liquid crystal compounds (3). By combining a plurality of polymerizable liquid crystal compounds, liquid crystal properties may be temporarily maintained even at a temperature below the liquid crystal-crystal phase transition temperature.

[0071] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition of the present invention is preferably 40 to 99.9 mass% with respect to the solid content of the polymerizable liquid crystal composition, more preferably 60 to 98 mass%, and even more preferably 70 to 95 mass%. When the content of the polymerizable liquid crystal compound is within the above range, the orientation of the polymerizable liquid crystal compound tends to increase. Furthermore, the term "solid content" as used herein refers to the total amount of components excluding volatile components such as solvents from the polymerizable liquid crystal composition, and hereinafter, when the term "solid content" is used in this specification, it likewise refers to the total amount of components excluding volatile components such as solvents from the composition to be targeted.

[0072] The polymerizable liquid crystal composition of the present invention comprises a dichroic pigment. Here, a dichroic pigment refers to a pigment having a property in which the absorbance in the direction of the long axis of the molecule and the absorbance in the direction of the short axis are different. The dichroic pigment used in the present invention is not particularly limited as long as it has the above property, and may be a dye or a pigment. Two or more types of dyes or pigments may be used in combination, or a dye and a pigment may be used in combination.

[0073] As a dichroic pigment, the maximum absorption wavelength (λ) in the range of 300 to 700 nm MAX It is desirable to have ). Examples of such dichroic pigments include acridin pigment, oxazine pigment, cyanine pigment, naphthalene pigment, azo pigment, and anthraquinone pigment.

[0074] Examples of azo dyes include monoazo dyes, bis-azo dyes, tris-azo dyes, tetrakis-azo dyes, and stilbenazo dyes, and bis-azo dyes and tris-azo dyes are preferred, and examples include the compound represented by formula (I) (hereinafter also referred to as “compound (I)”).

[0075] K 1-( N=NK 2 ) p -N=NK 3 (I)

[0076] [Equation (I), K 1 and K 3 represents, independently, a phenyl group that may have substituents, a naphthyl group that may have substituents, a phenyl benzoate ester group that may have substituents, or a monovalent complex ring that may have substituents. K 2 represents a p-phenylene group that may have substituents, a naphthalene-1,4-diyl group that may have substituents, a 4,4'-stilbenylene group that may have substituents, or a divalent complex ring that may have substituents. p represents an integer from 0 to 4. If p is an integer greater than or equal to 2, multiple K 2 They may be identical or different. In the range exhibiting absorption in the visible spectrum, -N=N- bonds may be substituted with -C=C-, -COO-, -NHCO-, or -N=CH- bonds.

[0077] Examples of monovalent complex ring groups include groups obtained by removing one hydrogen atom from complex ring compounds such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole. Examples of divalent complex ring groups include groups obtained by removing two hydrogen atoms from the above complex ring compounds.

[0078] K 1 and K 3 The phenyl group, naphthyl group, phenyl benzoate ester group and monovalent heterocyclic ring group in, and K 2The substituents optionally provided by the p-phenylene group, naphthalene-1,4-diyl group, 4,4'-stilbenylene group and the divalent complex ring in the above are: an alkyl group having 1 to 20 carbon atoms, an alkyl group having 1 to 20 carbon atoms having a polymerizable group, an alkenyl group having 1 to 4 carbon atoms; an alkoxy group having 1 to 20 carbon atoms having methoxy, ethoxy, butoxy, etc.; an alkoxy group having 1 to 20 carbon atoms having a polymerizable group; a fluoroalkyl group having 1 to 4 carbon atoms having a trifluoromethyl group, etc.; a cyano group; a nitro group; a halogen atom; Examples include substituted or unsubstituted amino groups such as amino groups, diethylamino groups, and pyrrolidino groups (a substituted amino group refers to an amino group having one or two alkyl groups having 1 to 6 carbon atoms, an amino group having one or two alkyl groups having 1 to 6 carbon atoms having a polymerizable group, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanedyl group having 2 to 8 carbon atoms. An unsubstituted amino group is -NH2). In addition, examples of the above polymerizable groups include (meth)acryloyl groups, (meth)acryloyloxy groups, etc.

[0079] Among dichroic pigments, azo pigments are desirable for the production of polarizing films with excellent polarization performance because they have high linearity. Therefore, in one embodiment of the present invention, the dichroic pigment included in the polymerizable liquid crystal composition is preferably an azo pigment. The polymerizable liquid crystal composition of the present invention has an excellent effect of suppressing photodegradation of the dichroic pigment in the polarizing film when a polarizing film is formed. For this reason, it is advantageous to be able to exhibit the effects of the present invention particularly significantly when using dichroic pigments that are susceptible to photodegradation due to light such as ultraviolet rays in sunlight, such as azo pigments. Furthermore, for dichroic pigments that are prone to aggregation among pigments, such as azo pigments having a divalent complex ring group, a high effect of suppressing photodegradation is obtained by using the antioxidant described below.

[0080] The content of the dichroic pigment in the polymerizable liquid crystal composition of the present invention can be appropriately determined depending on the type of dichroic pigment used. In one embodiment of the present invention, the content of the dichroic pigment, in total amount, is preferably 0.1 to 50 parts by mass, more preferably 0.1 to 20 parts by mass, and even more preferably 0.1 to 12 parts by mass, with respect to 100 parts by mass of the polymerizable liquid crystal compound. If the content of the dichroic pigment is within the above range, the orientation of the polymerizable liquid crystal compound is not easily disrupted, and a polarizing film having a high degree of orientation order can be obtained.

[0081] The polymerizable liquid crystal composition of the present invention is, Formula (1):

[0082] HO-A-(DB) n -E (1)

[0083] [Essence (1),

[0084] A and B are, independently of each other, a 1,4-phenylene group that may have a substituent or a cyclohexane-1,4-diyl group that may have a substituent, and

[0085] D are independently single bonds, -COO-, -OCO-, -S-, -O-, -CR=CR-, and

[0086] E is a straight-chain or branched alkyl group or alkoxy group, and

[0087] n is 1 or 2, and when n=1, B is a cyclohexane-1,4-diyl group that may have substituents, and when n=2, among the multiple B, at least one is a cyclohexane-1,4-diyl group that may have substituents.

[0088] It includes an antioxidant (1) represented by. As the antioxidant (1), it may include only one type, or may include a combination of two or more types.

[0089] The antioxidant (1) comprises two or more ring structures in its molecular structure, at least one of which is a cyclohexane-1,4-diyl group. In formula (1), when n=1, B is a cyclohexane-1,4-diyl group that may have a substituent, and preferably a cyclohexane-1,4-diyl group that does not have a substituent. When n=1, A may be a 1,4-phenylene group that may have a substituent or a cyclohexane-1,4-diyl group that may have a substituent, but preferably a 1,4-phenylene group that may have a substituent, and more preferably a 1,4-phenylene group that does not have a substituent. When n=2, at least one of the multiple B is a cyclohexane-1,4-diyl group that may have a substituent, and it is preferable that the B bonded to group E is a cyclohexane-1,4-diyl group that may have a substituent. It is more preferable that the cyclohexane-1,4-diyl group included as B is a cyclohexane-1,4-diyl group that does not have any substituents. When n=2, A may be a 1,4-phenylene group that may have substituents or a cyclohexane-1,4-diyl group that may have substituents, but preferably it is a 1,4-phenylene group that may have substituents, and more preferably it is a 1,4-phenylene group that does not have substituents.

[0090] D in formula (1) is independently, preferably a single bond, -COO-, -OCO-, or -O-, more preferably a single bond or -O-, and even more preferably a single bond.

[0091] E in Formula (1) is preferably a straight-chain or branched alkyl group having 1 to 12 carbon atoms, or a straight-chain or branched alkoxy group having 1 to 12 carbon atoms. Examples of straight-chain or branched alkyl groups having 1 to 12 carbon atoms include methyl group, ethyl group, propyl group, isopropyl group, butyl group, tert-butyl group, pentyl group, hexyl group, 2-ethylhexyl group, heptyl group, octyl group, nonyl group, decyl group, undecyl group, dodecyl group, etc. Examples of straight-chain or branched alkoxy groups having 1 to 12 carbon atoms include methoxy group, ethoxy group, propoxy group, butoxy group, pentyloxy group, hexyloxy group, octyloxy group, 2-ethylhexyloxy group, nonyloxy group, decyloxy group, undecyloxy group, dodecyloxy group, etc. E is more preferably a straight-chain or branched alkyl group having 1 to 12 carbon atoms, and even more preferably a straight-chain alkyl group having 1 to 12 carbon atoms.

[0092] In formula (1), n ​​is 1 or 2, preferably 1.

[0093] Antioxidants that are structurally similar or similar to polymerizable liquid crystal compounds tend to be orderedly oriented together with the polymerizable liquid crystal compounds in the liquid crystal state. Because of this, the intermolecular distance between the dichroic pigment existing in a state subsumed by the polymerizable liquid crystal compound is shortened, making it easier to obtain an inhibitory effect against photodegradation of the dichroic pigment. On the other hand, even if an antioxidant is structurally similar or similar to the polymerizable liquid crystal compound, it may be difficult to shorten the intermolecular distance between the dichroic pigment and the antioxidant, making it difficult to secure higher polarization performance. In the present invention, by using an antioxidant (1) having a specific molecular structure represented by formula (1), the inhibitory effect against photodegradation of the dichroic pigment can be further improved. Although the reason is not necessarily clear, for example, if the linearity or rigidity of the molecular structure of the antioxidant becomes excessively high, the antioxidants may tend to aggregate with each other. It is presumed that when antioxidants aggregate within a polymerizable liquid crystal composition, it becomes difficult for them to be oriented together with the polymerizable liquid crystal compound. Consequently, the intermolecular distance between the antioxidant and the dichroic pigment encapsulated within the polymerizable liquid crystal compound tends to increase, making it difficult for the antioxidant to act sufficiently on the dichroic pigment. Furthermore, it is presumed that the inclusion of a bulky cyclohexane backbone in the molecular structure of the antioxidant, which reduces planarity, prevents the aggregation of highly planar dichroic pigments, thereby consequently improving the compatibility between the antioxidant and the dichroic pigment.

[0094] In one embodiment of the present invention, the antioxidant (1) is formula (2):

[0095] SP3 a / ( SP2 a +SP3 a ) ≥ 0.25 (2)

[0096] [Essence (2), SP3 ais the number of SP3 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP2 a is the number of SP2 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant.

[0097] It is preferable that the antioxidant satisfies [the equation]. If the antioxidant (1) satisfies [the equation] (2), the antioxidant (1) is easily oriented in an orderly manner together with the polymerizable liquid crystal compound in the polymerizable liquid crystal composition, thereby reducing the intermolecular distance between the dichroic pigment and the antioxidant (1). As a result, the antioxidant (1) acts sufficiently, leading to an improvement in the photodegradation suppression effect of the dichroic pigment. SP3 in [the equation] (2). a / ( SP2 a +SP3 a The value of ) is more preferably 0.30 or higher, even more preferably 0.50 or higher, and usually 1.00 or lower.

[0098] When a polymerizable liquid crystal composition comprises two or more antioxidants (1), it is preferable that at least one of them is an antioxidant (1) satisfying the above formula (2), and all of them may be antioxidants (1) satisfying the formula (2). In one embodiment of the present invention, the content of the antioxidant (1) satisfying the formula (2) is preferably 51 mass% or more, more preferably 70 mass% or more, and even more preferably 90 mass% or more, based on the total mass of the total antioxidant (1), and the total antioxidant (1) in the polymerizable liquid crystal composition may be an antioxidant (1) satisfying the formula (2).

[0099] The weight average molecular weight of the antioxidant (1) is preferably 600 or less, more preferably 500 or less, and even more preferably 400 or less. If the weight average molecular weight of the antioxidant (1) is 600 or less, the antioxidant can be placed near the dichroic pigment without significantly disturbing the orientation of the polymerizable liquid crystal compound, thereby further improving the photodegradation suppression effect of the dichroic pigment. In addition, if the weight average molecular weight of the antioxidant (1) is 400 or less, it is more preferable because it becomes difficult to have absorption in the visible light wavelength region, thereby allowing for more effective reduction of the degradation of polarization performance. The weight average molecular weight of the antioxidant (1) is preferably 150 or more, and more preferably 180 or more. If the weight average molecular weight of the antioxidant (1) is above the above lower limit, it tends to be difficult to sublimate or volatilize during the drying process, etc., during film formation, and a sufficient amount of antioxidant (1) can be present in the obtained liquid crystal cured film.

[0100] As for antioxidants (1), specifically, the following compounds may be used as examples.

[0101] [Chemical Formula 1]

[0102]

[0103] [Chemical Formula 2]

[0104]

[0105] [Chemical Formula 3]

[0106]

[0107] [Chemical Formula 4]

[0108]

[0109] [Chemical Formula 5]

[0110]

[0111] [Chemical Formula 6]

[0112]

[0113] [Chemical Formula 7]

[0114]

[0115] [Chemical Formula 8]

[0116]

[0117] [Chemical Formula 9]

[0118]

[0119] [Chemical Formula 10]

[0120]

[0121] [Chemical Formula 11]

[0122]

[0123] [Chemical Formula 12]

[0124]

[0125] The content of the antioxidant (1) in the polymerizable liquid crystal composition of the present invention is preferably 0.1 to 15 parts by mass with respect to 100 parts by mass of the polymerizable liquid crystal compound, more preferably 0.3 to 12 parts by mass, even more preferably 0.5 to 8 parts by mass, and particularly preferably 0.5 to 5 parts by mass or less. If the content of the antioxidant (1) is greater than or equal to the lower limit value above, photodegradation of the dichroic pigment can be effectively suppressed. In addition, if the content of the antioxidant (1) is less than or equal to the upper limit value above, the orientation of the polymerizable liquid crystal compound is not easily disrupted, and a high suppression effect against photodegradation of the dichroic pigment can be expected.

[0126] In one embodiment of the present invention, the polymerizable liquid crystal composition is given by formula (5):

[0127] |(SP3 a / ( SP2 a +SP3 a ))―(SP3 b / ( SP2 b +SP3 b )| ≤ 0.30 (5)

[0128] [Essence (5), SP3 a is the number of SP3 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP2 a is the number of SP2 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP3 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 It is the number of SP3 carbons among all carbons forming the ring represented by, and SP2 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 [It is the number of SP2 carbons among all carbons forming the ring represented by]

[0129] It is desirable to satisfy [the formula]. In other words, it is desirable to select an antioxidant (1) and a polymerizable liquid crystal compound such that the polymerizable liquid crystal composition satisfies [the formula] (5). When the polymerizable liquid crystal composition satisfies [the formula] (5), the polymerizable liquid crystal compound in the polymerizable liquid crystal composition is easily oriented in an orderly manner together with the antioxidant (1), so that the intermolecular distance between the dichroic pigment and the antioxidant (1) can be effectively reduced. As a result, the antioxidant (1) acts sufficiently in the polymerizable liquid crystal composition, leading to an improvement in the photodegradation suppression effect of the dichroic pigment.

[0130] |(SP3 in Equation (5) a / ( SP2 a +SP3 a ))―(SP3 b / ( SP2 b +SP3 bThe value of )| is more preferably 0.25 or less, and even more preferably 0.20 or less. |(SP3 a / ( SP2 a +SP3 a ))―(SP3 b / ( SP2 b +SP3 b The lower limit of )| may be 0, preferably 0.05 or higher, more preferably 0.1 or higher. In Equation (5), SP3 b / ( SP2 b +SP3 b The value of ) and SP3 a / ( SP2 a +SP3 a The magnitude of the values ​​of ) is not particularly limited and either one may be larger, but in one embodiment of the present invention, SP3 b / ( SP2 b +SP3 b The value of ) is SP3 a / ( SP2 a +SP3 a It is preferable that the value be smaller than ). Also, in another embodiment, SP3 b / ( SP2 b +SP3 b The value of ) and SP3 a / ( SP2 a +SP3 a The value of ) may be the same. In addition, when the polymerizable liquid crystal composition contains two or more antioxidants and / or polymerizable liquid crystal compounds, it is preferable that each polymerizable liquid crystal compound satisfies Equation (5) in relation to the antioxidant with a higher content, and it is more preferable that all antioxidants and polymerizable liquid crystal compounds satisfy Equation (5).

[0131] In the polymerizable liquid crystal composition of the present invention containing an antioxidant (1), the amount of unreacted monomer in the cured film formed by the composition can be reduced. Although the reason for this is not necessarily clear, it is presumed that the antioxidant (1) is structurally difficult to deactivate, and when it is included, the antioxidant functions sufficiently within the composition, making it easier for the polymerization of the polymerizable liquid crystal compound to proceed. In one embodiment of the present invention, the amount of unreacted monomer in the cured film formed by the polymerizable liquid crystal composition is preferably less than 6%, more preferably 5.9% or less, and even more preferably 5.8% or less. The amount of unreacted monomer can be measured, for example, by an infrared total reflection absorption spectrum and can be calculated based on the following formula (6). In detail, it can be obtained by the method described in the example below.

[0132] (P' / P0)×100 (6)

[0133] [In the formula, P' represents the P value in a plane perpendicular to the thickness direction on the side where the alignment film of the cured film is stacked, and P0 represents the P value of the polymerizable liquid crystal compound used. The P value is expressed as I(1) / I(2), where I(1) represents the peak intensity derived from the in-plane angle-changing vibration of the ethylenetic unsaturated bond by infrared total reflection absorption spectrum measurement, and I(2) represents the peak intensity derived from the stretching vibration of the unsaturated bond of the orientation ring by infrared total reflection absorption spectrum measurement.]

[0134] The polymerizable liquid crystal composition of the present invention may include other antioxidants other than antioxidant (1) as long as they do not impede the effects of the present invention. Examples of such other antioxidants include primary antioxidants such as phenolic compounds, alicyclic alcohol compounds, and amine compounds, which are different from conventionally known antioxidants, for instance, antioxidant (1). In order to secure high effects of the present invention, in one embodiment of the present invention, the content of other antioxidants other than antioxidant (1) is preferably 20 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, and particularly preferably 3 mass% or less, for example 1 mass% or less, based on the total mass of all antioxidants.

[0135] The polymerizable liquid crystal composition of the present invention may contain a polymerization initiator.

[0136] A polymerization initiator is a compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, and a photopolymerization initiator is preferred in that it can initiate a polymerization reaction under lower temperature conditions. Specifically, a photopolymerization initiator capable of generating active radicals or acids by the action of light can be cited, and among these, a photopolymerization initiator that generates radicals by the action of light is preferred. The polymerization initiator can be used alone or in combination of two or more types.

[0137] Specific examples of photopolymerization initiators include the following.

[0138] Benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether;

[0139] Hydroxyacetophenone compounds such as oligomers of 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-〔4-(2-hydroxyethoxy)phenyl〕propan-1-one, 1-hydroxycyclohexylphenylketone, and 2-hydroxy-2-methyl-1-〔4-(1-methylvinyl)phenyl〕propan-1-one;

[0140] α-aminoacetophenone compounds such as 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one, 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one;

[0141] Oxime ester compounds such as 1,2-octanedione, 1-[4-(phenylthio)-,2-(O-benzoyloxime)], ethanol, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-,1-(O-acetyloxime);

[0142] Acylphosphine oxide compounds such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide;

[0143] Benzophenone compounds such as benzophenone, o-methyl benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenylsulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone;

[0144] Dialcoxiacetophenone compounds such as diethoxyacetophenone;

[0145] 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-〔2-(5-methylfuran-2-yl)ethenyl〕-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-〔2-(furan-2-yl)ethenyl〕-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-〔2-(4-diethylamino-2-methylphenyl)ethenyl〕-1,3,5-triazine and Triazine-based compounds such as 2,4-bis(trichloromethyl)-6-〔2-(3,4-dimethoxyphenyl)ethenyl〕-1,3,5-triazine. The photopolymerization initiator may be appropriately selected, for example, in relation to the polymerizable liquid crystal compound included in the polymerizable liquid crystal composition from the above photopolymerization initiator.

[0146] In addition, commercially available photopolymerization initiators may be used. Commercially available polymerization initiators include Irgacure (registered trademark) 907, 184, 651, 819, 250, and 369, 379, 127, 754, OXE01, OXE02, OXE03 (manufactured by BASF); Omnirad BCIM, Esacure 1001M, Esacure KIP160 (manufactured by IDM Resins BV); Seikool (registered trademark) BZ, Z, and BEE (manufactured by Seiko Chemical Co., Ltd.); Kayacure (registered trademark) BP100, and UVI-6992 (manufactured by Dow Chemical Corporation); Examples include ADEKA Optomer SP-152, N-1717, N-1919, SP-170, ADEKA Arcles NCI-831, ADEKA Arcles NCI-930 (manufactured by ADEKA Co., Ltd.); TAZ-A, and TAZ-PP (manufactured by Nippon Siebell Hegner Co., Ltd.); and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).

[0147] When a polymerizable liquid crystal composition contains a polymerization initiator, the content thereof can be appropriately determined according to the type and amount of the polymerizable liquid crystal compound included in the polymerizable liquid crystal composition, but is preferably 1 to 15 parts by mass, more preferably 1 to 10 parts by mass, even more preferably 2 to 8 parts by mass, and particularly preferably 4 to 8 parts by mass per 100 parts by mass of the polymerizable liquid crystal compound. If the content of the polymerization initiator is within the above range, the polymerization reaction of the polymerizable liquid crystal compound can be carried out without significantly disturbing the orientation of the polymerizable liquid crystal compound.

[0148] When a polymerizable liquid crystal composition contains a polymerization initiator, the content thereof can be appropriately determined according to the type and amount of the polymerizable liquid crystal compound included in the polymerizable liquid crystal composition, but 0.1 to 30 parts by mass per 100 parts by mass of the polymerizable liquid crystal compound is preferred, 0.5 to 10 parts by mass is more preferred, and 0.5 to 8 parts by mass is even more preferred. If the content of the polymerizable initiator is within the above range, polymerization can be carried out without disturbing the orientation of the polymerizable liquid crystal compound.

[0149] The polymerizable liquid crystal composition of the present invention comprises a leveling agent. The leveling agent has the function of adjusting the fluidity of the polymerizable liquid crystal composition and making the coating film obtained by applying the polymerizable liquid crystal composition flatter; specifically, a surfactant may be used. As for the leveling agent, at least one selected from the group consisting of a leveling agent having a polyacrylate compound as a main component and a leveling agent having a fluorine atom-containing compound as a main component is preferred. The leveling agent may be used alone or in combination of two or more types.

[0150] Examples of leveling agents with polyacrylate compounds as the main component include “BYK-350”, “BYK-352”, “BYK-353”, “BYK-354”, “BYK-355”, “BYK-358N”, “BYK-361N”, “BYK-380”, “BYK-381”, and “BYK-392” (BYK Chemie).

[0151] Leveling agents with fluorine atom-containing compounds as the main component include “Megapac (registered trademark) R-08”, “R-30”, “R-90”, “F-410”, “F-411”, “F-443”, “F-445”, “F-470”, “F-471”, “F-477”, “F-479”, “F-482”, and “F-483” (DIC Corp.); “Suplon (registered trademark) S-381”, “S-382”, “S-383”, “S-393”, “SC-101”, “SC-105”, “KH-40”, and “SA-100” (AGC Seimi Chemical Corp.); Examples include “E1830”, “E5844” (Daikin Fine Chemical Research Institute, Inc.); “F-Top EF301”, “F-Top EF303”, “F-Top EF351”, and “F-Top EF352” (Mitsubishi Material Electronics Chemical Co., Ltd.).

[0152] The content of the leveling agent in the polymerizable liquid crystal composition of the present invention is preferably 0.05 to 5 parts by mass per 100 parts by mass of the polymerizable liquid crystal compound, and more preferably 0.05 to 3 parts by mass. When the content of the leveling agent is within the above range, it is easy to horizontally align the polymerizable liquid crystal compound, and non-uniformity does not occur easily, so there is a tendency to obtain a smoother polarizing film.

[0153] The polymerizable liquid crystal composition of the present invention may contain additives other than polymerization initiators and leveling agents. Examples of other additives include photosensitive agents, release agents, stabilizers, coloring agents such as bluening agents, flame retardants, and lubricants. When the polymerizable liquid crystal composition contains other additives, the content of the other additives is preferably greater than 0% and less than or equal to 20 mass% with respect to the solid content of the polymerizable liquid crystal composition, more preferably less than or equal to 10 mass%, and even more preferably less than or equal to 5 mass%.

[0154] The polymerizable liquid crystal composition of the present invention may include a solvent. Adding a solvent to the polymerizable liquid crystal composition facilitates coating, and consequently, often makes it easier to form a polarizing film. In particular, since compounds that generally exhibit smectic liquid crystal properties have high viscosity, including a solvent is advantageous in terms of coating properties, handling properties, etc. The solvent can be appropriately selected according to the solubility of the polymerizable liquid crystal compound and the dichroic pigment, and may include, for example, alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, ethyl lactate; and ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone, methyl isobutyl ketone; Examples include aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorinated hydrocarbon solvents such as chloroform and chlorobenzene. These solvents may be used individually or in combination of two or more types.

[0155] The content of the solvent can be appropriately determined depending on the type of polymerizable compound, dichroic pigment, antioxidant, etc. used, but is preferably 100 to 1900 parts by mass, more preferably 150 to 900 parts by mass, and even more preferably 180 to 600 parts by mass, with respect to 100 parts by mass of the solid component constituting the polymerizable liquid crystal composition.

[0156] The polymerizable liquid crystal composition of the present invention can typically be prepared by mixing and stirring a polymerizable liquid crystal compound, a dichroic pigment and an antioxidant, and, if necessary, the additives and solvents described above.

[0157] The polymerizable liquid crystal composition of the present invention can be preferably used in the manufacture of polarizing films because it has an excellent inhibitory effect on the photodegradation of dichroic pigments and can yield a polarizing film in which a time-dependent degradation of polarization performance is unlikely to occur. The present invention also targets a polarizing film which is a cured film of the polymerizable liquid crystal composition of the present invention.

[0158] A polarizing film with a high degree of orientation order can be manufactured using the polymerizable liquid crystal composition of the present invention.

[0159] In polarizing films with a high degree of orientation order, Bragg peaks derived from higher-order structures, such as hexatic or crystal phases, are obtained in X-ray diffraction measurements.

[0160] A Bragg peak refers to a peak originating from a plane periodic structure of molecular orientation. Accordingly, in a polarizing film formed from the polymerizable liquid crystal composition of the present invention, it is preferable that the polymerizable liquid crystal compound or its polymer be oriented such that the polarizing film exhibits a Bragg peak in X-ray diffraction measurements, and it is more preferable that the molecules of the polymerizable liquid crystal compound be oriented in a "horizontal orientation" that absorbs light. In the present invention, a polarizing film having a plane periodic interval of molecular orientation of 3.0 to 6.0 Å is preferred. A high degree of orientation order exhibiting a Bragg peak can be achieved by controlling the type of polymerizable liquid crystal compound used, the type and amount of antioxidant, the type and amount of dichroic pigment, etc.

[0161] As described above, by incorporating an antioxidant (1) in relation to the polymerizable liquid crystal compound, a high inhibitory effect against photodegradation of the dichroic pigment is obtained while maintaining the high orientation order of the polymerizable liquid crystal compound. Because of this, a polarizing film with excellent polarization performance and a low risk of degradation of polarization performance over time can be obtained.

[0162] The polarizing film of the present invention is, for example, a film of the polymerizable liquid crystal composition of the present invention.

[0163] Removing the solvent from the above film,

[0164] Raising the temperature above the temperature at which a polymerizable liquid crystal compound transitions to a liquid phase, and then lowering the temperature to cause the polymerizable liquid crystal compound to transition to a liquid phase (e.g., smectic liquid crystal), and

[0165] Polymerizing a polymerizable liquid crystal compound while maintaining the above liquid crystal phase (e.g., smectic liquid crystal).

[0166] It can be manufactured by a method including.

[0167] The formation of a film of a polymerizable liquid crystal composition can be carried out by applying a polymerizable liquid crystal composition, in particular, a polymerizable liquid crystal composition with viscosity adjusted by adding a solvent, onto a substrate or an alignment film described later.

[0168] The substrate is typically a transparent substrate. When the substrate is not installed on the display surface of a display element, for example, when a laminate from which the substrate has been removed from a polarizing film is installed on the display surface of a display element, the substrate does not need to be transparent. A transparent substrate refers to a substrate having transparency capable of transmitting light, particularly visible light, and transparency refers to a characteristic in which the transmittance for light rays with wavelengths ranging from 380 to 780 nm is 80% or more. Specific examples of transparent substrates include light-transmitting resin substrates. Resins constituting the light-transmitting resin substrate include polyolefins such as polyethylene and polypropylene; cyclic olefin resins such as norbornene-based polymers; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid esters; polyacrylic acid esters; cellulose esters such as triacetylcellulose, diacetylcellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; and polysulfone. Examples include polyethersulfone; polyetherketone; polyphenylene sulfide and polyphenylene oxide. In terms of ease of availability and transparency, polyethylene terephthalate, polymethacrylic acid ester, cellulose ester, cyclic olefin resin, or polycarbonate are preferred. Cellulose ester is a material in which some or all of the hydroxyl groups contained in cellulose are esterified, and it is readily available on the market. In addition, cellulose ester substrates are also readily available on the market. Examples of commercially available cellulose ester substrates include “Fujitak Film” (Fuji Photo Film Co., Ltd.); “KC8UX2M”, “KC8UY”, and “KC4UY” (Konica Minolta Opto Co., Ltd.).

[0169] The thickness of the substrate is typically 5 to 300 μm, preferably 20 to 200 μm, and more preferably 20 to 100 μm, because if it is too thin, the strength decreases and processability tends to decline.

[0170] Known methods for applying a polymerizable liquid crystal composition to a substrate, etc. include spin coating, extrusion, gravure coating, die coating, bar coating, applicator coating, and printing methods such as flexographic methods.

[0171] Next, a dry film is formed by removing the solvent by drying, under conditions where the polymerizable liquid crystal compound contained in the film obtained from the polymerizable liquid crystal composition is not polymerized. Examples of drying methods include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0172] In addition, to phase transition the polymerizable liquid crystal compound into a liquid phase, the temperature is raised above the temperature at which the polymerizable liquid crystal compound transitions into a liquid phase, and then lowered to phase transition the polymerizable liquid crystal compound into a liquid phase (e.g., smectic liquid crystal). This phase transition may be performed after the removal of the solvent from the coating film, or simultaneously with the removal of the solvent.

[0173] By polymerizing a polymerizable liquid crystal compound while maintaining its liquid crystal state, a cured film of the polymerizable liquid crystal composition is formed as a polarizing film. Photopolymerization is preferred as the polymerization method. In photopolymerization, the light irradiated onto the dried film is appropriately selected according to the type of photopolymerization initiator contained in the dried film, the type of polymerizable liquid crystal compound (in particular, the type of polymerizable group possessed by the polymerizable liquid crystal compound), and the amount thereof. Specific examples include one or more types of light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays, and γ-rays, or active electron beams. Among these, ultraviolet light is preferred because it is easy to control the progress of the polymerization reaction and allows the use of photopolymerization devices that are widely used in the field. It is also desirable to select the type of polymerizable liquid crystal compound or photopolymerization initiator contained in the polymerizable liquid crystal composition so that photopolymerization is possible by ultraviolet light. In addition, the polymerization temperature can be controlled by irradiating light while cooling the dried film with an appropriate cooling means during polymerization. By employing such a cooling means, polymerization of the polymerizable liquid crystal compound can be carried out at a lower temperature, allowing a polarizing film to be formed appropriately even if a substrate with relatively low heat resistance is used. A patterned polarizing film can also be obtained by performing masking or development during photopolymerization.

[0174] Examples of light sources for the above active energy lines include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in a wavelength range of 380 to 440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, metal halide lamps, etc.

[0175] UV irradiation intensity is typically 10 to 3,000 mW / cm² 2The ultraviolet irradiation intensity is preferably an intensity in a wavelength range effective for activating the photopolymerization initiator. The irradiation time is typically 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and even more preferably 10 seconds to 1 minute. When irradiated once or multiple times with such ultraviolet irradiation intensity, the integrated light quantity is 10 to 3,000 mJ / cm² 2 , preferably 50 to 2,000 mJ / cm² 2 , more preferably 100 to 1,000 mJ / cm² 2 am.

[0176] By performing photopolymerization, the polymerizable liquid crystal compound is polymerized while maintaining a liquid crystal state, preferably a smectic state, more preferably a higher-order smectic state, to form a polarizing film. The polarizing film obtained by polymerizing the polymerizable liquid crystal compound while maintaining a smectic liquid crystal state has the advantage of having high polarization performance compared to a conventional host-guest type polarizing film, that is, a polarizing film formed in a nematic liquid crystal state, in conjunction with the action of the dichroic dye. In addition, it has the advantage of having excellent strength compared to a film coated only with a dichroic dye or a lyotropic liquid crystal.

[0177] The thickness of the polarizing film can be appropriately selected according to the applied display device, and is preferably 0.1 to 10 μm, more preferably 0.3 to 4 μm, and even more preferably 0.5 to 3 μm.

[0178] It is preferable that the polarizing film be formed on the alignment film. The alignment film has an orientation regulating power that aligns the polymerizable liquid crystal compound in a desired direction. The alignment film preferably has solvent resistance so as not to dissolve upon application of a composition containing the polymerizable liquid crystal compound, and also has heat resistance during the removal of the solvent or heat treatment for the orientation of the polymerizable liquid crystal compound. Examples of such alignment films include an alignment film containing an oriented polymer, a photoalignment film, a groove alignment film having an uneven pattern or multiple grooves on its surface, and a stretched film stretched in the orientation direction; however, from the perspective of the precision of the alignment angle and quality, a photoalignment film is preferred.

[0179] A photoalignment film is typically obtained by applying a composition (hereinafter also referred to as a "composition for forming a photoalignment film") comprising a polymer or monomer having photoreactive groups and a solvent to a substrate and irradiating polarized light (preferably polarized UV). The photoalignment film is more preferable in that the direction of the orientation regulating force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.

[0180] A photoreactive group refers to a group that generates liquid crystal orientation ability upon light irradiation. Specifically, it may include a group involved in photoreactions that are the origin of liquid crystal orientation ability, such as molecular orientation induction, isomerization, dimerization, photocrosslinking, or photodecomposition reactions, which are generated by light irradiation. Among these, a group involved in dimerization or photocrosslinking is preferred due to its excellent orientation. As a photoreactive group, a group having an unsaturated bond, particularly a double bond, is preferred, and a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) is particularly preferred.

[0181] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bis-azo groups, forma groups, and groups having azoxybenzene structures. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and alkyl halide groups.

[0182] Among these, photoreactive groups involved in photodimerization reactions are preferred, and cinnamoyl groups and chalcone groups are preferred in that the amount of polarized light irradiation required for photoorientation is relatively small, and it is easy to obtain a photoorientation film with excellent thermal stability and stability over time. As for the polymer having photoreactive groups, it is particularly preferred that the terminal portion of the polymer side chain has a cinnamoyl group having a cinnamic acid structure.

[0183] A photo-aligned organic layer can be formed on a substrate by applying a composition for forming a photo-aligned film onto the substrate. As for the solvent included in the composition, the same as the solvent previously exemplified as a solvent that can be used when forming a polarizing film may be cited, and it can be appropriately selected depending on the solubility of the polymer or monomer having a photoreactive group.

[0184] The content of a polymer or monomer having a photoreactive group in a composition for forming a photoalignment film can be appropriately adjusted depending on the type of polymer or monomer or the thickness of the intended photoalignment film, but it is preferable to have at least 0.2 mass% with respect to the mass of the composition for forming a photoalignment film, and a range of 0.3 to 10 mass% is more preferable. Within a range where the properties of the photoalignment film are not significantly impaired, the composition for forming a photoalignment film may include polymer materials such as polyvinyl alcohol or polyimide or a photosensitizer.

[0185] A method for applying a composition for forming a photoalignment film to a substrate is the same as a method for applying a polymerizable liquid crystal composition to a substrate. Methods for removing the solvent from the applied composition for forming a photoalignment film include natural drying, ventilation drying, heat drying, and vacuum drying.

[0186] To irradiate polarized light, the method may involve directly irradiating polarized UV light onto a composition for forming a photoalignment film coated on a substrate from which the solvent has been removed, or by irradiating polarized light from the substrate side and transmitting the polarized light. It is particularly preferable that the polarized light be substantially parallel light. The wavelength of the irradiated polarized light is preferably in a wavelength range in which the photoreactive groups of a polymer or monomer having photoreactive groups can absorb light energy. Specifically, UV (ultraviolet) light in the wavelength range of 250 to 400 nm is particularly preferred. Examples of light sources used for the irradiation of polarized light include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, and ultraviolet lasers such as KrF and ArF, with high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps being more preferred. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are preferred because they have a high emission intensity of ultraviolet light at a wavelength of 313 nm. Polarized UV can be irradiated by passing light from the above light source through a suitable polarizer. As such a polarizer, a polarizing filter, a polarizing prism such as a Glen Thomson or Glen Taylor, or a wire grid type polarizer can be used.

[0187] In addition, when performing rubbing or polarization irradiation, if masking is performed, multiple regions (patterns) with different liquid crystal orientation directions may be formed.

[0188] An alignment film or a groove alignment film containing an oriented polymer can be manufactured according to conventional known techniques, such as those described in Japanese Patent Publication No. 2019-133148. In addition, commercially available alignment film materials may be used as is.

[0189] The thickness of the alignment film (an alignment film or photoalignment film containing an oriented polymer) is typically in the range of 10 to 10,000 nm, preferably in the range of 10 to 1,000 nm, more preferably in the range of 500 nm or less, even more preferably in the range of 10 to 200 nm, and particularly preferably in the range of 50 to 150 nm.

[0190] The polarizing film of the present invention has excellent absorbance stability when exposed to sunlight and has an excellent effect of suppressing the degradation of polarization performance over time. For this reason, a circular polarizing plate comprising the polarizing film and the phase difference film of the present invention can be preferably used in various display devices. A display device is a device having a display mechanism and includes a light-emitting element or a light-emitting device as a light source. Examples of display devices include liquid crystal display devices, organic electroluminescence (EL) display devices, inorganic electroluminescence (EL) display devices, touch panel display devices, electron emission display devices (electric field emission display devices (FED, etc.), surface field emission display devices (SED)), electronic paper (a display device using electronic ink or an electrophoretic element), plasma display devices, projection display devices (display devices having a grating light valve (GLV) display device or a digital micromirror device (DMD)), and piezoelectric ceramic displays. Liquid crystal display devices include any of the following: transmissive liquid crystal display devices, transmissive liquid crystal display devices, reflective liquid crystal display devices, direct-view liquid crystal display devices, and projection liquid crystal display devices. These display devices may be display devices that display two-dimensional images, or stereoscopic display devices that display three-dimensional images. The polarizing film of the present invention is particularly suitable for use in organic EL display devices or touch panel display devices.

[0191] Examples

[0192] The present invention will be explained in more detail below through examples. Unless otherwise specified, "%" and "parts" in the examples are mass % and mass parts.

[0193] 1. Fabrication of polarizing films

[0194] (1) Preparation of a composition for forming a photo-alignment film

[0195] A composition for forming a photo-alignment film was obtained by mixing the following components described in Japanese Patent Publication No. 2013-033249 and stirring the resulting mixture at 80°C for 1 hour.

[0196] · Photooriented polymers: Part 2

[0197] [Chemical Formula 13]

[0198]

[0199] · Solvent: o-xylene 98 parts

[0200] (2) Preparation of a polymerizable liquid crystal composition

[0201] A polymerizable liquid crystal composition (1) was obtained by mixing the following components and stirring at 80°C for 1 hour. The following azo dyes were used as dichroic dyes. In addition, SP3 of the polymerizable liquid crystal compounds listed in Table 1 b / ( SP2 b +SP3 b The value of ) was the value of polymerizable liquid crystal compound 1 and polymerizable liquid crystal compound 2, respectively, and both were 0.33.

[0202] · Polymerizable liquid crystal compound 1:90 parts

[0203] [Chemical Formula 14]

[0204]

[0205] · Polymerizable liquid crystal compound 2:10 parts

[0206] [Chemical Formula 15]

[0207]

[0208] · Dichroic pigment 1 : Azo pigment 3.2 parts

[0209] [Chemical Formula 16]

[0210]

[0211] · Dichroic Pigment 2: Azo Pigment 3.1 Part

[0212] [Chemical Formula 17]

[0213]

[0214] · Dichroic Pigment 3: Azo Pigment 3.1 Part

[0215] [Chemical Formula 18]

[0216]

[0217] · Dichroic Pigment 4: Azo Pigment 3.1 Part

[0218] [Chemical Formula 19]

[0219]

[0220] · Polymerization initiator: 6 parts

[0221] α-acetophenone compound (ESACURE ONE, manufactured by DKSH Japan Co., Ltd.)

[0222] · Leveling Agent: 1.2 parts

[0223] Polyacrylate compound (BYK-361N; manufactured by BYK-Chemie)

[0224] · Solvent: o-xylene 400 parts

[0225] In addition, polymerizable liquid crystal compositions (2) to (4) were obtained in the same manner as polymerizable liquid crystal composition (1), except that 2 parts of a compound having the structure described in Table 1 were mixed with 100 parts by mass of the polymerizable compound as an antioxidant in the polymerizable liquid crystal composition (1).

[0226] Structure of Antioxidants

[0227] The structure of the antioxidant used in the examples and comparative examples is as follows.

[0228] · Antioxidant 1 :

[0229] [Chemical Formula 20]

[0230]

[0231] · Antioxidant 2 :

[0232] [Chemical Formula 21]

[0233]

[0234] · Antioxidant 3 :

[0235] [Chemical Formula 22]

[0236]

[0237] 2. Evaluation of polarizing films

[0238] (1) Preparation of a sample for evaluating absorbance stability (glass laminate with a cycloolefin resin film attached)

[0239] (i) Example 1

[0240] A glass substrate was used as a substrate for forming a photoalignment film, and after performing corona treatment on the film surface, the composition for forming the photoalignment film was applied and dried at 120°C to obtain a dried film. Polarized UV was irradiated onto this dried film to form a photoalignment film, thereby obtaining glass with a photoalignment film attached. The irradiation with polarized UV was performed using a UV irradiation device (SPOT CURE SP-7; manufactured by Ushio Electric Co., Ltd.) under conditions where the intensity measured at a wavelength of 365 nm was 100 mJ.

[0241] On a glass laminate to which a photoalignment film obtained as above is attached, a polymerizable liquid crystal composition (1) is applied by the bar coating method (#9 30 mm / s), and the polymerizable liquid crystal compound is phase-transitioned into a liquid phase by heating and drying in a drying oven at 120°C for 1 minute, and then cooled to room temperature to phase-transition the polymerizable liquid crystal compound into a smectic liquid crystal state. Subsequently, a UV irradiation device (SPOT CURE SP-7; manufactured by Ushio Electric Co., Ltd.) is used to apply an exposure amount of 1000 mJ / cm² 2 By irradiating a layer formed of a polymerizable liquid crystal composition (1) with ultraviolet light (based on 365 nm), the polymerizable liquid crystal compound contained in the dried film was polymerized while maintaining the smectic liquid crystal state of the polymerizable liquid crystal compound, and a polarizing film was formed from the dried film. At this time, the thickness of the polarizing film was measured by a laser microscope (OLS3000 manufactured by Olympus Co., Ltd.) and was 2.3 μm. The laminate produced in this way includes a polarizing film, a light alignment film, and a glass substrate (hereinafter also referred to as a "glass laminate with a polarizing film attached"). X-ray diffraction measurements were performed on this glass laminate with a polarizing film attached using an X-ray diffraction device X'Pert PRO MPD (manufactured by Spectris Co., Ltd.), and a sharp diffraction peak (Bragg peak) with a peak full width at half maximum (FWHM) of approximately 0.17° was obtained around 2θ=20.2°. In addition, equivalent results were obtained with incidence from the direction perpendicular to the rubbing. The order period (d) obtained from the peak position is approximately 4.4 Å, and it was confirmed that a structure reflecting a higher-order smectic phase is formed.

[0242] Subsequently, a cycloolefin-based resin film with a thickness of 13 μm (Zeonora Film G+, manufactured by Nippon Zeon Co.) is laminated onto the polarizing film side of the glass laminate with the polarizing film attached through an acrylic adhesive (thickness 25 μm, manufactured by Lintec Co.) to obtain a glass laminate with a cycloolefin-based resin film attached, comprising a cycloolefin-based resin film / acrylic adhesive / polarizing film / light alignment film / glass substrate.

[0243] (ii) Example 2 and Comparative Examples 1 and 2

[0244] Except for replacing the polymerizable liquid crystal composition (1) with the polymerizable liquid crystal compositions (2) to (4) respectively, a glass laminate with the cycloolefin resin film of Example 2 and Comparative Examples 1 and 2 attached was prepared in the same order as Example 1.

[0245] (2) Calculation of absorbance stability

[0246] The absorbance of a glass laminate with a cycloolefin resin film attached was measured as follows. The absorbance of the dichroic pigment in the orientation direction (absorption axis direction) was measured in the wavelength range of 380 to 680 nm in 2 nm steps using the double beam method with a spectrophotometer (UV-3150 manufactured by Shimadzu Corporation) equipped with a folder with a polarizer, and A1 was set at a wavelength of 520 nm in the absorption axis direction. In addition, to eliminate the contribution of light loss due to surface reflection of the laminate, zero point correction was performed at 800 nm, where there is no light absorption, after setting the measurement sample.

[0247] Next, the glass laminate with the attached cycloolefin resin film is placed into a light resistance tester (CI4400; manufactured by ATLAS) such that the cycloolefin resin film side becomes the irradiation surface, and the irradiation intensity at a wavelength of 520 nm is 2.4 W / m² 2Light irradiation was performed for 240 hours under the conditions. After removing the glass laminate with the attached cycloolefin resin film from the light resistance tester, the absorbance A2 in the absorption axis direction was measured again by the above method, and the absorbance stability represented by the following equation (7) was calculated. The results are shown in Table 1.

[0248] A1 / (A1―A2) (7)

[0249] [In the formula, A1 represents the absorbance at a wavelength of 520 nm along the absorption axis before the lightfastness test, and A2 represents the absorbance at a wavelength of 520 nm along the absorption axis after the lightfastness test.]

[0250] (3) Calculation of unreacted monomer ratio

[0251] By measuring the total infrared absorption spectrum of the glass laminate with the above-mentioned polarizing film, the unreacted monomer ratio represented by the following equation (6) was calculated. The results are shown in Table 1.

[0252] (P' / P0)×100 (6)

[0253] [In the formula, P' represents the P value in a plane perpendicular to the thickness direction on the side where the alignment layer of the polarizing film is stacked. P0 represents the P value of the polymerizable liquid crystal compound. The P value is expressed as I(1) / I(2). I(1) represents the peak intensity derived from the in-plane angle-changing vibration of the ethylenically unsaturated bond by infrared total reflection absorption spectrum measurement, and I(2) represents the peak intensity derived from the stretching vibration of the unsaturated bond of the orientation ring by infrared total reflection absorption spectrum measurement.]

[0254]

[0255] It has been confirmed that the polarizing film formed from the polymerizable liquid crystal composition of the present invention has high absorbance stability and good light resistance.

Claims

Claim 1 Polymerizable liquid crystal compound, dichroic pigment, and formula (1): HO-A-(DB) n -E (1) A polymerizable liquid crystal composition comprising an antioxidant represented by the formula (1), wherein A and B are independently a 1,4-phenylene group that may have a substituent or a cyclohexane-1,4-diyl group that may have a substituent, D is independently a single bond, -COO-, -OCO-, -S-, -O-, -CR=CR-, E is a straight-chain or branched alkyl group or an alkoxy group, n is 1 or 2, and when n=1, B is a cyclohexane-1,4-diyl group that may have a substituent, and when n=2, among the multiple B, at least one is a cyclohexane-1,4-diyl group that may have a substituent. Claim 2 In claim 1, the polymerizable liquid crystal compound is a polymerizable liquid crystal composition having a cyclohexane backbone. Claim 3 In claim 1, the antioxidant is formula (2): SP3 a / ( SP2 a +SP3 a ) ≥ 0.25 (2)[Equation (2), SP3 a is the number of SP3 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP2 a A polymerizable liquid crystal composition satisfying [the number of SP2 carbons among all carbons forming a ring represented by A and B in Formula (1) representing the antioxidant above]. Claim 4 In claim 1, the polymerizable liquid crystal compound is, formula (3): U 1 -V 1 -W 1 -X 1 -Y 1 -X 2 -Y 2 -X 3 -W 2 -V 2 -U 2 (3)[Equation (3) of, X 1 , X 2 and X 3 ...independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein the hydrogen atom included in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, a C1-4 alkyl group, a C1-4 fluoroalkyl group, a C1-4 alkoxy group, a cyano group, or a nitro group, and the carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom (provided that X 1 , X 2 and X 3 At least one of them is a 1,4-phenylene group that may have a substituent or a cyclohexane-1,4-diyl group that may have a substituent),Y 1 and Y 2 is, independently of each other, a single coupling or a 2-valent connector, and U 1 Silver, representing a hydrogen atom or a polymerizable group, U 2 represents a polymerizable group, and W 1 and W 2 is, independently of each other, a single coupling or a 2-valent connector, and V 1 and V 2 A polymerizable liquid crystal composition comprising a compound represented by [a carbon alkandyl group having 1 to 20 carbon atoms that may have substituents independently thereof, wherein the -CH2- constituting the alkandyl group may be substituted with -O-, -CO-, -S-, or NH-]. Claim 5 In claim 1, the polymerizable liquid crystal compound is formula (4): SP3 b / ( SP2 b +SP3 b ) ≥ 0.25 (4)[Equation (4), SP3 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 It is the number of SP3 carbons among all carbons forming the ring represented by, and SP2 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 A polymerizable liquid crystal composition satisfying [the number of SP2 carbons among all carbons forming a ring represented by]. Claim 6 In claim 1, Equation (5): |(SP3 a / ( SP2 a +SP3 a ))―(SP3 b / ( SP2 b +SP3 b )| ≤ 0.30 (5)[Equation (5), SP3 a is the number of SP3 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP2 a is the number of SP2 carbons among all carbons forming the ring represented by A and B in Formula (1) representing the antioxidant, and SP3 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 It is the number of SP3 carbons among all carbons forming the ring represented by, and SP2 b is X in formula (3) representing the polymerizable liquid crystal compound. 1 , X 2 and X 3 A polymerizable liquid crystal composition satisfying [the number of SP2 carbons among all carbons forming a ring represented by]. Claim 7 A polarizing film, which is a cured film of the polymerizable liquid crystal composition described in claim 1. Claim 8 In claim 7, a polarizing film exhibiting a Bragg peak in X-ray diffraction measurements.